Microdrill with variations in thickness of diamond coating. (3rd March 2016) - Lei, X.; Wang, L.; Shen, B.; Sun, F.
Abstract : In this study, microcrystalline diamond films with varied thicknesses (1·2, 2·5, 4 and 7 μm) are deposited on flat samples and microdrills. The Raman results show that the top layer of thicker diamond films on flat samples exhibit relatively lower compressive residual stress and favourable diamond purity. However, with increased thickness, the multiple radial and diagonal microcracks along with significant diamond coating detachment are easier to be formed in thicker diamond coatings. These results can be applied for analysing the mechanisms on the coating delamination for the thicker diamond coatings and the worse wear resistance for the thinner ones deposited on microdrills during graphite machining processes. The microcrystalline diamond coated microdrill with 2·5 μm coating thickness reveals the best cutting performance due to its robust rigidity for preventing the detachment of diamond films as well as the relatively good wear resistance.